Development of methyl ester using batch enzymatic reaction - Ibrahim, Kamarul Asri; Ali, Mohamad Wijayanuddin; Mohd. Ekhsan, Abdul Wahid (Faculty of Chemical & Natural Resources Engineering, 1992)
The objective of this research is to determine the production of methyl ester by using several combination of batch processes. In the study, palm olein and methanol were utilized as a substrates and lipase enzyme as a catalyst. The result showed that the composition of 30% methanol and 70% palm olein gave the highest composition of methyl ester.